Targeting ADAM17 Sheddase Activity in Cancer - Rossello, Armando; Nuti, Elisa; Ferrini, Silvano; Fabbi, Marina (Current Drug Targets, 2016)
A disintegrin and metalloprotease (ADAM)17 is a sheddase, capable of releasing the ectodomains of membrane proteins such as growth factors (e.g. Epidermal Growth Factor Receptor ligands), cytokines and their receptors, adhesion and signaling molecules. These activities regulate several physiological and pathological processes including inflammation, tumor growth and metastatic progression. In this review, we will summarize ADAM17 biology and focus on its role in cancer and the possible usage of ADAM17 inhibitors in cancer therapy. Recent achievements in this area include the development of small molecule metalloprotease inhibitors with enhanced specificity for ADAM17, monoclonal antibodies, and synthetic short RNA molecules for gene silencing. These approaches successfully inhibited cancer cell growth and invasiveness or sensitized them to cytotoxic drugs, ionizing radiations or targeted therapies, in preclinical studies. These findings suggest the repositioning of ADAM17 inhibitors, which have yet proven unsuccessful as anti-inflammatory agents, for the development of new anti-cancer therapies, particularly in EGFR ligand-dependent cancers. Future studies should address ADAM17 inhibitors as short-term treatments in combination with different anti-cancer therapies.
Keywords: ADAM17